The role of Interleukin-22 in controlling virus infections at mucosal surfaces - Guo, Cuncai; Boulant, Steeve; Stanifer, Megan (Journal of interferon & cytokine research, 2024)
Interleukin-22 (IL-22) is an IL-10 family cytokine that has gained interest in recent years owing to multiple functions in regulating immune response such as inflammation, protection against infection, and tissue repair. Many cell types can produce IL-22, such as innate lymphoid cells, T cells, and natural killer cells. In addition, cytokines or chemicals such as IL-7, IL-23, and aryl hydrocarbon receptor can regulate IL-22-producing cells and control IL-22 production. Only a few cells, such as respiratory epithelial cells, intestinal epithelial cells, and hepatocytes, can respond to IL-22 because of the restricted distribution of IL-22 receptor in these cell types. This restricted expression of the IL-22 receptor in epithelial cells has been suggested to play a key role in sustaining homeostasis in these tissues, particularly in the context of virus infection. This review will focus on the production and regulation of IL-22 and its roles in antiviral activity in the respiratory and intestinal tract.
Gesehen am 26.11.2024